Prospects of Phage Application in the Treatment of Acne Caused by Propionibacterium acnes - Jończyk-Matysiak, Ewa; Weber-Dąbrowska, Beata; Żaczek, Maciej; Międzybrodzki, Ryszard; Letkiewicz, Sławomir; Łusiak-Szelchowska, Marzanna; Górski, Andrzej (Frontiers in Microbiology, 2017)
Propionibacterium acnes is associated with purulent skin infections, and it poses a global problem for both patients and doctors. Acne vulgaris (acne) remains a problem due to its chronic character and difficulty of treatment, as well as its large impact on patients' quality of life. Due to the chronic course of the disease, treatment is long lasting, and often ineffective. Currently there are data regarding isolation of P. acnes phages, and there have been numerous studies on phage killing of P. acnes, but no data are available on phage application specifically in acne treatment. In this review, we have summarized the current knowledge on the phages active against P. acnes described so far and their potential application in the treatment of acne associated with P. acnes. The treatment of acne with phages may be important in order to reduce the overuse of antibiotics, which are currently the main acne treatment. However, more detailed studies are first needed to understand phage functioning in the skin microbiome and the possibility to use phages to combat P. acnes.